Śrīmadbhāgavatadaśamaskandhajanmaprakarṇaśrīsubodhinīṭippaṇyoḥ Prakāśaḥ - Puruṣottamacaraṇagosvāmin (Caukhambā-Saṃskrta-granthamālā, 1915)
Classical gloss on the 10th chapter of Sobodhinī, Śuddhādvaita commentary on Bhāgavatapurāṇa, by Vallabhācārya, 1479-1531?